2018
DOI: 10.1590/1806-9061-2017-0706
|View full text |Cite
|
Sign up to set email alerts
|

Broiler Chicken Meat Inspection Data in Brazil: A First Glimpse into an Animal Welfare Approach

Abstract: We aimed to study the potential use of carcass condemnation data of broiler chicken slaughterhouses in Brazil as indicators in an animal welfare monitoring program, and to identify points to be addressed to increase data reliability. Data from 2010 to 2015 in the states of Paraná (PR), Santa Catarina (SC) and Rio Grande do Sul (RS) were used. Fractures and bruising were recorded together, representing the most prevalent welfare problem, followed by skin lesion or inflammation. In PR, progressive increases on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 20 publications
3
19
0
Order By: Relevance
“…Brazil is one of the largest producers and exporters of chicken meat in the world [ 6 ]. Information about resistance to biocide agents, virulence factors of strains, its genetic diversity, and their ability to form biofilms in an industrial environment are extremely important, considering the difficulty of Salmonella control and the constant need for knowledge about the emergence of this microorganism in the country, which can contribute to the strategic development of measures for the control and prevention of salmonellosis at a global level [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Brazil is one of the largest producers and exporters of chicken meat in the world [ 6 ]. Information about resistance to biocide agents, virulence factors of strains, its genetic diversity, and their ability to form biofilms in an industrial environment are extremely important, considering the difficulty of Salmonella control and the constant need for knowledge about the emergence of this microorganism in the country, which can contribute to the strategic development of measures for the control and prevention of salmonellosis at a global level [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted between the states of Paraná, Santa Catarina and Rio Grande do Sul, evaluating the condemnation of birds, it was observed that injuries were the main cause of condemnation in 2015, followed by dermatoses. These same authors report that the third highest incidence of condensation is associated with dorsal skull myopathy [49]. In the State of Paraná, which slaughter more than the others in absolute numbers, the percentage of convictions increases.…”
Section: Animal Welfare: Possible Changes Due To the Occurrence Of Wooden Breast And White Stripingmentioning
confidence: 92%
“…Also, meat mortality and inspection data are considered to establish maximum values of stocking density. Dermatitis, parasitic infections and systemic diseases should also be measured to identify signs of poor well-being [49].…”
Section: Animal Welfare: Possible Changes Due To the Occurrence Of Wooden Breast And White Stripingmentioning
confidence: 99%
“…Among their responsibilities, the official veterinarian is responsible for inputting the daily condemnation data into the Management Information System of the Federal Inspection Service (MISFIS) (BRASIL, 1998(BRASIL, , 2017. Considering the importance of Brazil as a global producer and supplier of animal protein, studies have used these data to analyze and propose improvements to the sector (Muchon et al, 2019;Souza et al, 2018;Souza et al, 2021).…”
Section: Introductionmentioning
confidence: 99%